Experimental study of low-cycle fatigue of S30408 welded joints with strain strengthening. Issue 2 (April 2021) - Si, Jun; Ren, Facai; Ren, Bin
Abstract: With the change of energy consumption structure, cryogenic liquids are increasingly widely used, such as liquefied natural gas (LNG), liquid hydrogen, liquid nitrogen, etc. Austenitic stainless steel is widely used in fabrication of cryogenic temperature pressure vessels as a kind of material with good lower temperature resistance. It is difficult to give full play to the high tensile strength and high plasticity reserve of austenitic stainless steel by using conventional design methods, which results in material waste and cost increase. The strain strengthening technology of austenitic stainless steel is the more effective method to realize the lightweight design and manufacture of cryogenic pressure vessel and reduce the cost. Fatigue damage is one of the typical failure modes of cryogenic pressure vessels. For the fatigue design of conventional pressure vessels, there are detailed standards, but there are few specific provisions for the fatigue design of strain strengthening pressure vessels. In this paper, experimental study on the low-cycle fatigue behavior of S30408 welded joints with 7% and 9% pre-tensile deformation were carried out.